Marriage without borders : transnational spouses in neoliberal Senegal - Hannaford, Dinah (Philadelphia : University of Pennsylvania Press, 2017)
In popular songs, televised media, news outlets, and online venues, a jabaaru immigré ("a migrant's wife") may be depicted as an opportunistic gold-digger, a forsaken lonely heart, or a naïve dupe. Her migrant husband also faces multiple representations as profligate womanizer, conquering hero, heartless enslaver, and exploited workhorse. These depictions point to fluctuating understandings of gender, status, and power in Senegalese society and reflect an acute uneasiness within this coastal West African nation that has seen an exodus in the past thirty-five years, as more men and women migrate out of Senegal in hope of a better financial future. Marriage Without Borders is a multi-sited study of Senegalese migration and marriage that showcases contemporary changes in kinship practices across the globe engendered by the neoliberal demand for mobility and flexibility. Based on ten years of ethnographic research in both Europe and Senegal, the book examines a particular social outcome of economic globalization: transnational marriages between Senegalese migrant men living in Europe and women at home in Senegal. These marriages have grown exponentially among the Senegalese, as economic and social possibilities within the country have steadily declined. More and more, building successful social lives within Senegal seems to require reaching outside the country, through either migration or marriage to a migrant. New kinds of affective connection, and disconnection, arise as Senegalese men and women reshape existing conceptions of spousal responsibility, filial duty, Islamic piety, and familial care. Dinah Hannaford connects these Senegalese transnational marriages to the broader pattern of flexible kinship arrangements emerging across the global south, arguing that neoliberal globalization and its imperative for mobility extend deep into the family and the heart and stretch relationships across borders.
Frontmatter -- Contents -- Preface -- Introduction -- Chapter 1. Bitim Rëw -- Chapter 2. Precarity, Care Work, and Lives Suspended -- Chapter 3. Loneliness, Elegance, and Reproductive Labor -- Chapter 4. Mobility, Surveillance, and Infidelity -- Chapter 5. Sex, Love, and Modern Kinship -- Chapter 6. Reunions -- Conclusion: The Handmaiden of Neoliberalism -- Appendix: Scope and Methods of the Study -- Notes -- Bibliography -- Index -- Acknowledgments.
In English.
Description based upon online resource; title from PDF title page (viewed April 9th, 2024).
JSTOR
Keywords: Intercountry marriage -- Senegal -- History -- 21st century; Transnationalism -- History -- 21st century; Senegalese -- Marriage customs and rights -- History -- 21st century; Senegalese -- Europe -- History -- 21st century; Senegal -- Emigration and immigration -- History -- 21st century; Mariage interethnique -- Sénégal -- Histoire -- 21e siècle.; Transnationalisme -- Histoire -- 21e siècle.; Sénégalais -- Europe -- Histoire -- 21e siècle.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE / Anthropology / General; Emigration and immigration; Intercountry marriage; Senegalese; Transnationalism; Europe; Senegal; Anthropology; Gender studies: women & girls; Sociology: family & relationships; Society; 2000-2099; History